Rectus Femoris Muscle Composition: Association with Sports Performance and Playing Position in Female Soccer Players - Valera-Calero, Juan Antonio; Varol, Umut; Fernández-de-las-Peñas, César; López-de-Uralde-Villanueva, Ibai; Plaza-Manzano, Gustavo; Gual-Pizarro, Jaime (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2022)
Background Quadriceps muscle plays a relevant role in soccer as its function is determinant for sprinting, jumping and striking the ball. Although ultrasound demonstrated to be useful in risk of injury prevention and monitoring post-injury rehabilitation, no studies analyzed the ultrasound muscle histology with sports performance tests. We aimed to analyze the correlation between ultrasound findings related to rectus femoris morphology and composition with sports performance indicators and to analyze sociodemographic, sports performance and ultrasound differences according to playing position.Methods An observational study was conducted at the CFF OLYMPIA soccer club (Madrid, Spain). Twenty-two semi-professional female soccer players were enrolled in this study. Sociodemographic data, bilateral ultrasound measurements of the rectus femoris muscle and sports performance tests (Counter Movement Jump -CMJ-, The Sprint Repeat Ability -SRA-, and one Repetition Maximum -1RM-) were collected.Results No correlations between ultrasound imaging and sports performance indicators were found. Significant correlations between cross-sectional area and perimeter with age (p<0.05) and fatty infiltration with body mass index and tight perimeter (p<0.05) were seen. No muscle ultrasound morphology or quality differences were found between the playing positions (p>0.05). Finally, most of the functional tests showed no between-position differences (except SRA between goalkeepers and attackers).Conclusion Although muscle morphology and quality are associated with demographic features, US should not be used as a predictor of sports performance in female football players since no association between US and sports performance were observed. Similar US and functional test scores were obtained among the different playing positions.
Keywords: Ultrasound Imaging; Quadriceps; Cross-sectional Area; Echo-Intensity; Sports performance; Soccer